Classification of the Hyrcanian forest vegetation, Northern Iran - Gholizadeh, Hamid; Naqinezhad, Alireza; Chytrý, Milan; Jansen, Florian (Applied vegetation science, 2020)
Aims To develop forest vegetation classification at the level of alliances and associations across the Hyrcanian ecoregion, Northern Iran, and to explore the effects of main environmental and geographic gradients on their distribution. Location Hyrcanian ecoregion, Northern Iran. Methods A database of 1,597 vegetation plots of mostly 400 m2 in size with a total of 802 vascular plant taxa was established, covering the whole geographic range of the Hyrcanian forests at altitudes ranging from −22 to 2,850 m a. s. l. An expert system was developed for automatic classification of vegetation plots into alliances and associations. Detrended correspondence analysis (DCA) and canonical correspondence analysis (CCA) were used to determine the most important environmental and geographic gradients affecting species composition. Results Twenty‐one associations and seven alliances of these forests, belonging to five orders and four classes, were defined. Among them, eleven associations and five alliances were described as new syntaxa. Alnion glutinosae and Smilaco excelsae‐Alnion barbatae, both distributed in the lowland belt, include swamp and wet forests, respectively. Parrotio persicae‐Carpinion betuli and Alnion subcordatae are respectively mesic and wet forests of the submontane belt. Solano kieseritzkii‐Fagion orientalis is a mesic beech forest in the montane belt, and finally, Quercion macrantherae, an open oak forest, and Centaureo hyrcanicae‐Carpinion orientalis, a dry hornbeam forest, occur in the upper‐montane belt. DCA and CCA analyses showed that the distribution of these alliances and associations is mainly related to altitude and mean annual temperature. Conclusions Based on our results and comparison between the Hyrcanian and European forests, we propose a new, comprehensive syntaxonomic scheme for the Hyrcanian forests, supported by a classification expert system. Unlike previous studies, we linked the classification system to that of EuroVegChecklist because, though this area is outside of Europe, its vegetation is very similar to that of the European temperate forest vegetation. The Hyrcanian ecoregion in Northern Iran is an isolated area with a well‐developed biome of temperate broad‐leaved deciduous forest, containing many relict species. We provide the first comprehensive classification of these forests into alliances and associations across the whole ecoregion, based on a new database of 1,597 vegetation plots, and relate individual vegetation types to altitude, climate and soil conditions.